The Gross Agricultural Output of Portugal: A Quantitative, Unified Perspective, 1500-1850 - Jaime Reis (European Historical Economics Society (EHES), 2016)
This paper presents the first estimate to date of the anual output of Portugal's agriculture between 1500 and 1850. It adopts the well-known indirect approach, which uses a consumption function for agricultural products. Prices and wages for this come from a recently created data base. It also verifies the assumption that agricultural consumption is equal or very close to national output. The method for calculating the income variable in the function is innovative since labour supplied per worker is not constant over time as in many estimates. Instead, it is made to vary, reflecting the 'industrious revolution' which occurred in Portugal during much of the period considered. The main finding is that the country's agriculture displays a long-run upward trend, contrary to traditional stagnationist views. It was unable, however, to keep up with the even stronger concomitant growth of population. Food consumption consequently declined, sharply in the 16c. but more slowly in the 17c. It recovered during part of the 18c. but after the 1750s it slipped again and down to 1850 it lost all these welfare gains.
Keywords: N53; O13; Q10; 330; agricultural output; early modern Portugal; cycles; food consumption